Field Testing of Multispecies Probiotics on Health Status, Water Quality, and Productivity of Pacific White Shrimp (Litopenaeus vannamei) - Siregar, Lindah Erlia Safira; Rahardjo, Sinung; Rahayu, Tb. Haeru; Wiradana, Putu Angga (Universitas Gadjah Mada, 2026)
Shrimp farming has rapidly grown into a significant sector worldwide, providing economic benefits and high-quality food. Probiotics are widely used in shrimp farming to enhance growth and prevent diseases. However, reports on the field-scale application of multispecies probiotics in shrimp farming are minimal. This study aims to evaluate the effectiveness of multispecies probiotics on the health status, production performance, and water quality of L. vannamei shrimp farming at a field scale. L. vannamei post-larvae were reared in maintenance ponds. The shrimp seeds were stocked in 10 plots (50×50×2 m²) and acclimated for 7 days. Multispecies probiotics were administered after acclimatization, and health status parameters, production performance, and water quality were subsequently measured. The results indicated that multispecies probiotics combined with molasses and fermented bran were ineffective at preventing V. parahaemolyticus growth, as evidenced by the health status of L. vannamei. However, multispecies probiotics improved production performance and water quality through the end of the maintenance period. This study highlights the effectiveness of multispecies probiotics in enhancing production performance and water quality. Further research is needed to understand the mechanism of action of these probiotics in vannamei shrimp at a field scale.